Reading abstract expressionism : context and critique - Landau, Ellen G.; Landau, Ellen G. (Yale University Press, 2005)
"Abstract Expressionism is arguably the most important art movement in postwar America. Many of its creators and critics became celebrities, participating in heated public debates that were published in newspapers, magazines, and exhibition catalogues. This up-to-date anthology is the first comprehensive collection of key critical writings about Abstract Expressionism from its inception in the 1940s to the present day."--Jacket